Mitigation of marine debris from land: Formulation of the best options for managing marine debris in the coastal city of Manado, Indonesia - Warouw, Veibe; Mamuaja, Jane M.; Pane, Lindon R.; Maramis, Regina U.; Lasut, Markus T. (AQUATIC SCIENCE & MANAGEMENT, 2023)
Mitigation of marine debris in Manado City, the city which is situation in front of the Manado bay, is very important in order to prevent its effect on the coastal communities and as well as for the aesthetics point of view. That activities can directly protect the ecosystem of Bunaken Marine Park (BMP), and can become an important part of the marine waste management activities especially in supporting the commitment of Indonesian government to reducing plastic waste in the sea by 70% by 2025. For this reason, a marine waste management is needed and it should be prepared based on the academic study that are comprehensive and holistic as well as effective and efficient, and also suitable for environmental condition in Manado City. The study was aimed to formulate best options for the existing marine waste management in Manado City. By using qualitative-descriptive and content-analysis methods, four aspects of managemet were studied, and they are 1) public awareness, 2) institutional arrangements, 3) regulations, policies and management plans, and 4) waste management guidelines. The data obtained were quantitatively and qualitatively analyzed. The public awarenes was qualitatively analyzed by using two indicators, community concern and community preference. The existing marine waste management was presented based on studied aspects and the best option was proposed as recommendation for marine waste management in Manado City.